Design and engineering of nanogels for cancer treatment - Yallapu, Murali Mohan (2011)
Here, we provide a comprehensive insight into current advances in the use of nanogel-mediated chemotherapy for cancer treatment. Nanogels are composed of cross-linked three-dimensional polymer chain networks that are formed via covalent linkages or self-assembly processes. The porosity between the cross-linked networks of nanogels not only provides an ideal reservoir for loading drugs, oligonucleotides and imaging agents, but also protects them from environmental degradation and hazards. Here, we focus mainly on novel synthetic strategies and key considerations in the design of nanogel-based drug delivery systems for controlled and targeted cancer therapeutic applications.